Efficacy and safety of hybutimibe in combination with atorvastatin for treatment of hypercholesteremia among patients with atherosclerotic cardiovascular disease risk equivalent: A multicenter, randomized, double-blinded phase III study - Qi, Litong; Chen, Jiyan; Li, Xiaodong; Qi, Xiaoyong; Ding, Chunhua; Chen, Xiaoping; Gu, Xiang; Xiao, Wenliang; Zhao, Shuiping; Dong, Yugang; Zheng, Mingqi; Huang, Kai; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background To evaluate the safety and efficacy of hybutimibe plus atorvastatin for lipid control in hypercholesterolemia patients with atherosclerotic cardiovascular disease risk equivalent. Methods In this double-blind phase III study, we 1:1 randomly assigned 255 hypercholesterolemia patients with atherosclerotic cardiovascular disease to receive hybutimibe plus atorvastatin or placebo plus atorvastatin. The primary endpoint was the rate of change of plasma low-density lipoprotein-cholesterol (LDL-C) level at 12 weeks from baseline. The secondary endpoints were plasma total cholesterol (TC), triglyceride (TG), high-density lipoprotein-cholesterol (HDL-C), non-HDL-C, apoprotein (Apo) B, and 2-, 4-, 8-, and 12-week Apo A1 levels change rate and rates of change of plasma LDL-C levels at 2, 4, and 8 weeks from baseline. Results From April 2016 to January 2018, 128 in the hybutimibe plus atorvastatin group and 125 in the atorvastatin group were included in modified intention-to-treat (mITT) analysis. After 12 weeks of treatment, LDL-C level changed from 2.61 mmol/L (±0.30) at baseline to 2.18 mmol/L (±0.45) in the hybutimibe plus atorvastatin group and from 2.58 (±0.31) mmol/L to 2.40 (± 0.46) mmol/L in the atorvastatin group (P < 0.0001), in mITT. The change rate in the hybutimibe plus atorvastatin group was significantly higher than that in the atorvastatin group (P < 0.0001); the estimated mean rates of change were −16.39 (95% confidence interval: −19.04, −13.74) and −6.75 (−9.48, −4.02), respectively. Consistently, in per-protocol set (PPS) analysis, the rate of change of LDL-C in the hybutimibe plus atorvastatin group was significantly higher than that in atorvastatin group. Significant decreases in the change rates of non-HDL-C, TC, and Apo B at 2, 4, 8, and 12 weeks (all P < 0.05) were observed for hybutimibe plus atorvastatin, while the differences were not significant for HDL-C, TG, and Apo-A1 (all P > 0.05). During the study period, no additional side effects were reported. Conclusions Hybutimibe combined with atorvastatin resulted in significant improvements in LDL-C, non-HDL-C, TC, and Apo B compared with atorvastatin alone. The safety and tolerability were also acceptable, although additional benefits of hybutimibe plus atorvastatin were not observed compared with atorvastatin alone in HDL-C, TG, and Apo-A1.